STRATEGI SOSIALISASI PEMBERDAYAAN PAUD PKK AR-RAHMAN (Analisis Fungsionalisme Struktural di Desa Kandangan, Kecamatan Srengat, Kabupaten Blitar) - A Zahid A Zahid; Luluk Laila Sifa; Anis Fitriana; Nikmatul Ulviani; Khalimatu Sya’diyah; Ahmad Fajar Jabaludin (KAIBON ABHINAYA : JURNAL PENGABDIAN MASYARAKAT, 2020)
The importance of early childhood education has led the government to take action by issuing a policy to form the PADU Directorate (now called PAUD) in 2001. Under the auspices of the Directorate General of Education Outside School, the PADU Directorate is responsible for the development of PAUD in non-formal and formal education channels. However, the compilation reaches the community, socialization will require PAUD is still very minimal in the community who choose to send them directly to kindergarten or even at the elementary level. This is what happened in the Kandangan Community, in the discussion of PAUD for early childhood before entering a higher level. It is this dysfunction of PAUD Ar-Rahman that makes it interesting to study deeper, Why is there an inability to function in this PAUD.The method used is based on empowerment for PAUD management or management, the CBR (Community Based Research) method, using the analysis of Talcott Parsons' Structuralism Functionalism Theory. The theory used is a theory that focuses on structural work in understanding what strategies can be used in the development of PKK Ar-Rahman PAUD in Kandangan Village, Sregat District, Blitar Regency.From the results of this research, it can be concluded that after the door-to-door socialization activities. PAUD in Kandangan Village, PKK Ar-Rahman PAUD. Besides that, the community also understands that formal early childhood education is very important as an effort to support children's education for the future. The door-to-door socialization strategy is one of the socialization strategies undertaken as an effort to develop Ar-Rahman's PAUD because it will thus be in accordance with existing targets.